To determine which equation is true when the value of p is –6, we can substitute –6 for p in each equation and see which equation gives us a true statement.
A: 2(p + 4) = 4
Substituting –6 for p: 2(-6 + 4) = 4
Simplifying: 2(-2) = 4
-4 = 4
This is false.
B: 3p + 4 = –14
Substituting –6 for p: 3(-6) + 4 = –14
Simplifying: -18 + 4 = –14
-14 = –14
This is true when p = –6.
C: p^2 + 17 = 15
Substituting –6 for p: (-6)^2 + 17 = 15
Simplifying: 36 + 17 = 15
53 = 15
This is false.
D: 3p – 11 = –25
Substituting –6 for p: 3(-6) – 11 = –25
Simplifying: -18 - 11 = –25
-29 = –25
This is false.
Therefore, the equation that is true when the value of p is –6 is B: 3p + 4 = –14.
equation is true when the value of p is –6?
Responses
A 2(p + 4) = 42( p + 4) = 4
B 3p + 4 = –143 p + 4 = –14
C
p
2 + 17 = 15 p 2 + 17 = 15
D 3p – 11 = –25
1 answer